Stretchable multifunctional wearable system for real-time and on-demand thermotherapy of arthritis - Zehan Liu; Xihan Wang; Yiyang He; Weiqiang Hong; Peng Sun; Weitao Liu; Dong Ye; Zhuoqing Yang; Xuewen Wang; Mengxi Wu; Liding Wang; Junshan Liu (Microsystems & Nanoengineering)
Abstract Thermotherapy is a conventional and effective physiotherapy for arthritis. However, the current thermotherapy devices are often bulky and lack real-time temperature feedback and self-adjustment functions. Here, we developed a multifunctional wearable system for real-time thermotherapy of arthritic joints based on a multilayered flexible electronic device consisting of homomorphic hollow thin-film sensors and heater. The kirigami−serpentine thin-film sensors provide stretchability and rapid response to changes in environmental temperature and humidity, and the homomorphic design offers easy de-coupling of dual-modal sensing signals. Based on a closed-loop control, the thin-film Joule heater exhibits rapid and stable temperature regulation capability, with thermal response time < 1 s and maximum deviation < 0.4 °C at 45 °C. Based on the multifunctional wearable system, we developed a series of user-friendly gears and demonstrated programmable on-demand thermotherapy, real-time personal thermal management, thermal dehumidification, and relief of the pain via increasing blood perfusion. Our innovation offers a promising solution for arthritis management and has the potential to benefit the well-being of thousands of patients.